Regarding the Right to Creative Freedom in the Context of Conflict with Property Rights as Examplified by Street Art - Glotov, Sergiy (Teisė, 2022)
This article discusses the issue of evaluation of the street artists’ rights to their work from the point of view of the owner and the architect of the building through the prism of the rights of the latter. After all, upon the appearance of a graffiti, mural, or another street art work on someone’s property, the conflict of rights and interests between the aforesaid persons is inevitable. It is argued that a street artist cannot always claim the copyright holder status. And when they can, their copyright ranks last in the hierarchy of the rights of the concerned rights holders.